2017
DOI: 10.1002/mp.12619
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of a kilovoltage external beam radiotherapy system on phantoms and breast patients

Abstract: Although nonoptimized KVAT dose distributions presented here were of inferior quality to VMAT plans, this work has demonstrated the feasibility of delivering low-energy kilovoltage x-rays to lesions up to 4 cm in diameter to depths of 8.1 cm while sparing surrounding tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 18 publications
4
17
0
Order By: Relevance
“…Figure shows that the primary difference between the KVAT and VMAT breast treatment is the homogeneity of the dose within the lesion. The KVAT plan produced regions of higher dose within the PTV due to the overlap of the beamlets, a phenomenon which has been observed in previous work . This is not of concern as there has been evidence that a heterogeneous dose within the PTV may not be detrimental .…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Figure shows that the primary difference between the KVAT and VMAT breast treatment is the homogeneity of the dose within the lesion. The KVAT plan produced regions of higher dose within the PTV due to the overlap of the beamlets, a phenomenon which has been observed in previous work . This is not of concern as there has been evidence that a heterogeneous dose within the PTV may not be detrimental .…”
Section: Discussionsupporting
confidence: 59%
“…Figure is a rendering of one potential design of the KVAT system and illustrates the x‐ray source mounted on a slip‐ring gantry and the location of the patient on the treatment couch. Figure is a modified image from our previous work and illustrates the geometry of the KVAT transmission source and the geometry of KVAT radiation delivery. The x‐ray source MC model consists of a 60‐cm by 1‐cm tungsten transmission anode with an electromagnetically steered electron beam running at 200–225 keV for radiation therapy as well as lower energies for imaging.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above found dose rate can be compared, albeit roughly, to the simulated MC findings previously published for a 16.2 cm diameter water phantom. 13 In that study, the dose rate at 200 kV, 200 mA was found to be just over 150 cGy/min for a 4 cm lesion at the center of a 16.2 cm cylindrical water phantom. 13 Given the estimate dose rate as described above as shown in Figure 10, found as 66 cGy/min for 15.6 cm acrylic phantom at 145 kV, the dose rate is lower than the simulated values.…”
Section: Discussionmentioning
confidence: 88%
“…Proof-of-principle simulations were first used with a transmission anode design. These simulations for cylindrical water phantoms indicated that a skin sparing effect could be produced while delivering a dose rate up to 345 cGy/min for a 1-cm diameter spherical target, with dose rates decreasing at greater target size and depth [51].…”
Section: Kilovoltage X-ray Beam Arc Therapymentioning
confidence: 99%